Pornography in the Perspective of Islamic Criminal Law - Aulia, Redhina; Rizqi, Retanisa; Usmani, Sheikh Adnan Ahmed (Faculty of Sharia, IAIN Metro, 2023)
Social media is currently overgrowing, which certainly impacts people's lifestyles. However, these advances are often exploited, with cyberporn being one example. This essay seeks to evaluate and critique pornography from the point of view of Indonesian Islamic criminal law. Examining the application of criminal sanctions for pornography by Islamic criminal law, as well as the reasons why it is created and prohibited, is the aim of this study. This study examines laws and regulations with a normative legal approach. It is the study of normative juridical law. This research data set comes from legal sources. The research findings suggest several behaviors, weaknesses in judgment, constitutive consequences, additional circumstances, additional requirements for a criminal prosecution, and additional requirements for punishment that fall under the category of pornography crimes of Islamic criminal law. Criminal sanctions in Islamic law allow adultery and ta'zir as punishment for pornography offenders. Criminal acts in pornography include various forms, including sounds, moving images, animations, cartoons, conversations, body movements, and public performances containing sexual exploitation or obscene content that violates the norms of social decency.